y"(t) + 4y'(t) + 4y(t) = 4e-2t, y(0) = -1, y'(0) = 4
Characteristic equation corresponding to the given homogeneous differential equation
"y''(t)+4y'(t)+4y=0" is "r^2+4r+4=0"
"\\Rightarrow (r+2)^2=0\\Rightarrow r=-2,-2"
General solution to the homogeneous differential equation is
"y_{h}=c_{1}e^{-2t}+c_2te^{-2t}"
Use Method of variation of parameters to find the particular solution
Particular solution to the given differential equation is
"y_{p}=Au+Bv,u=e^{-2t},v={te^{-2t}}" where
"A=\\int \\frac{-vg(t)}{uv'-vu'}dt,B=\\int \\frac{ug(t)}{uv'-vu'}dt,g(t)=4e^{-2t}"
Find "uv'-vu'"
Now
"uv'-vu'=(e^{-2t})\\left [ e^{-2t}-2te^{-2t} \\right ]-(te^{-2t})(-2e^{-2t})=e^{-4t}-2te^{-4t}+2te^{-4t}=e^{-4t}"
"A=\\int \\frac{-e^{-2t}(4e^{-2t})}{e^{-4t}}dt=-4\\int dt=-4t"
"B=\\int \\frac{te^{-2t}(4e^{-2t})}{e^{-4t}}dt=4\\int(t) dt=\\frac{t^2}{2}"
Using the above, we get
"y_{p}=(-4t)(e^{-2t})+(\\frac{t^2}{2})({te^{-2t}})=-4te^{-2t}+\\frac{t^3}{2}e^{-2t}"
General solution to the given differential equation is
"y=y_{h}+y_{p}=c_{1}e^{-2t}+c_{2}te^{-2t}-4te^{-2t}+\\frac{t^3}{2}e^{-2t}"
Find the value of "c_{1}" and "c_{2}" using the given initial conditions "y(0)=-1,y'(0)=4"
"y=c_{1}e^{-2t}+c_{2}te^{-2t}-4te^{-2t}+\\frac{t^3}{2}e^{-2t}"
"\\Rightarrow y'(t)=-2c_{1}e^{-2t}+c_{2}(e^{-2t}-2te^{-2t})-4e^{-2t}+8te^{-4t}+\\frac{3t^2}{2}e^{-2t}-t^3e^{-2t}"
"y(0)=-1\\Rightarrow c_{1}+0=-1\\Rightarrow c_{1}=-1"
"y'(0)=4\\Rightarrow -2c_{1}+c_{2}(1-0)-4(1)+8(0)+0-0=4"
"\\Rightarrow -c_{1}+c_{2}=0\\Rightarrow c_{2}=-1"
Therefore, solution to the given differential equation is
"y=-e^{-2t}-te^{-2t}-4te^{-2t}+\\frac{t^3}{2}e^{-2t}"
Comments
Leave a comment